Evaluation of ERA5 reanalysis atmospheric water vapor variation in Algeria - Namaoui, Houaria (Geodetski vestnik, 2022)
In climate change context, the precipitable water vapour (PW) is key parameter of atmospheric process and dynamics and its variation is very high in space and time. It's accuracy is paramount for any geodetic or climatic study. The main objective of this study is to compute precipitable water vapour from ERA5 reanalysis for 4 stations in Algeria which have different types of climate. We opt for using integration method for different level of pressure with ERA5. The values of water vapour are also compared with radiosondes profiles. The results of this work shows good agreement with a correlation that is not less than not 0.95 and 0.70 compared as radiosondes profiles. The first results are encouraging, in particular for meteorological applications with good hope to introduce another dataset as GNSS to more understand the variation and behavior of water vapour over a long period of observation.
Keywords: Era 5; Era interim; GNSS; vodna para; water vapour